KOMUNIKASI UMAT BERBEDA AGAMA DI MEDIA SOSIAL (STUDI PADA YOUTUBE JEDA NULIS PROGRAM “INDONESIA RUMAH BERSAMA”) - Barkah, Desprianti (Dirasa Islamiyya: Journal of Islamic Studies, 2023)
Coexisting with people of other religions can create its own colours, although sometimes these differences can lead to friction or even conflict. In general, conflicts can be born from discrepancies between one party and another. This is common because of different perspectives and beliefs between religions.  Youtube can be a means of spreading the message of tolerance through communication between people of different religions. This research used a qualitative approach. The method was content analysis on various Jeda Nulis Youtube shows. The research findings were that cultural communication in religion refers to the way communication occurs within a religious group and is influenced by the values, beliefs, traditions, and cultural norms that exist in the religion. Cultural communication in religion is very important because it helps members of religious groups to interact, convey religious messages, and build a shared religious identity. In cultural communication in religion, it is important to understand and respect the cultural diversity that exists within the world's religions. Each religion is unique and has different ways of communicating, but all aim to convey religious messages, strengthen religious identity, and promote tolerance and understanding between religions.